The Moral Proverbs of Santob de Carrion : Jewish Wisdom in Christian Spain - Santob, de Carrión de los Condes, approximately 1290-approximately 1369 (Book collections on Project MUSE., 1987)
This is the first English translation of Santob do Carrion's Proverbios morales (Moral Proverbs) and also the first book-length study of that monumental work. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.